PREPARING STUDENT'S COMPETENCIES TO FACE THE CHALLENGES OF THE VUCA (VOLATILITY, UNCERTAINTY, COMPEXITY, AMBIGUITY) ERA - Sari, Dwi Novita; Soamole, Amrin; Marsella, Prasastiara Eka (Journal of Development Economics and Digitalization, Tourism Economics, 2024)
This qualitative study aims to identify the competencies required by students to navigate the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. The research was conducted through in-depth interviews with students and lecturers from public and private universities in Jakarta. The data collection method involved in-depth interviews to gather comprehensive insights into the competencies deemed essential for students. The data analysis was carried out using thematic analysis techniques, which facilitated the identification of recurring themes and patterns in the responses. The findings reveal eight key competencies that are critical for students in the VUCA environment: Leadership, Digital Literacy, Communication, Emotional Intelligence, Entrepreneurship, Global Citizenship, Problem Solving, and Team-working. Leadership is highlighted as the ability to inspire and motivate others, while Digital Literacy is seen as fundamental for understanding and utilizing evolving technologies. Communication skills, both verbal and non-verbal, along with Emotional Intelligence, are essential for building effective relationships and managing emotions in uncertain situations. Entrepreneurship is crucial for fostering innovation and managing risks, whereas Global Citizenship is important for understanding cross-cultural perspectives and social responsibility. Problem Solving and Team-working are identified as vital for facilitating collaboration and developing solutions to complex problems. The study underscores the interconnectedness of these competencies and their collective importance in equipping students to address the challenges of the VUCA era. By providing a detailed understanding of these competencies, this research contributes valuable insights into the skills that students need to succeed in a rapidly changing and uncertain world.